University Outreach Management: Assessment and Perspectives from the Case Study of the University’s Academic Week - Costa, Igor Dalepiane da; Fell, Lucas Alexandre; Tiadoro, Eduardo; Fialho, Matheus; Basso, Fábio; Bernardino, Maicon (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The Brazilian National Council of Education’s Resolution Nº. 7/2018 mandates the integration of outreach activities into higher education curricula, effective from 2023. This requirement has created a need for efficient solutions to manage and support outreach activities within universities. Problem: Managing outreach activities manually is challenging, often leading to inefficiencies and missed opportunities for student engagement. The absence of a comprehensive system for managing these activities makes it difficult for coordinators to track and validate students’ participation effectively. Solution: This study presents the development and evaluation of a web-based IS designed to support the management of outreach programs and projects within academic institutions, particularly focusing on use during large-scale events like an Academic Week. Theory of IS: The research is based on Soft Systems Theory (SST), which helps address the complex social and organizational issues involved in managing university outreach activities. Method: A case study method was employed during our university’s AcademicWeek, involving over 300 users. Data were collected through direct observation and a structured survey, utilizing the AttrakDiff technique to evaluate user satisfaction with usability and functionality. Summary of Results: The Web-based IS demonstrated effective support for managing outreach activities and received positive feedback from users. Key insights were collected, including suggestions to improve navigability, performance optimization, and user support materials. Contributions and Impact in the IS Area: This research contributes a tailored management Web-based IS that addresses specific needs in academic outreach, potentially enhancing the efficiency and accessibility of outreach activities. The findings provide valuable insights for further development and set the groundwork for similar applications in educational institutions.